2018
DOI: 10.4326/jjcvs.47.248
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Perigraft Seroma after Ascending Aorta Replacement That Was Cured by an Omental Pedicle Graft

Abstract: A 40-year-old man with a family history of Marfan syndrome was admitted to our hospital because of acute Stanford type A aortic dissection. He underwent a Bentall operation with an artificial vascular graft. Postoperative computed tomography revealed a low-density area around the graft in the ascending aorta and at the left subclavian artery cannulation site. He showed no symptoms and was discharged uneventfully. Five months after the operation, a pulsatile subdermal tumor appeared in the center of the median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Spartera et al reported postoperative perigraft fluid collection areas greater than 3.5 cm in diameter at 1 month after the operation in 19% of cases of aortic reconstruction, with postoperative perigraft fluid collection often noted [1]. However, a subcutaneous tumor due to development of a perigraft seroma after thoracic aortic surgery is an infrequently encountered complication, with only three cases reported thus far in literature [2][3][4]. In order to effectively treat this subcutaneous tumor, confirmation of diagnosis is important, and when it appears secondary to an anastomotic rupture, pseudoaneurysm, or graft infection, treatment must be performed as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spartera et al reported postoperative perigraft fluid collection areas greater than 3.5 cm in diameter at 1 month after the operation in 19% of cases of aortic reconstruction, with postoperative perigraft fluid collection often noted [1]. However, a subcutaneous tumor due to development of a perigraft seroma after thoracic aortic surgery is an infrequently encountered complication, with only three cases reported thus far in literature [2][3][4]. In order to effectively treat this subcutaneous tumor, confirmation of diagnosis is important, and when it appears secondary to an anastomotic rupture, pseudoaneurysm, or graft infection, treatment must be performed as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is made based on physical examination, blood test, bacterial culture of the tumor, CT, and radiodensity results, as well as other indications. However, Go et al reported a case with a perigraft seroma that appeared after a Bentall operation, in which artifacts seen in enhanced CT images were considered to be extravasation of contrast media and an anastomotic rupture was mistakenly diagnosed, resulting in a redo sternotomy [3].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment option of replacing the original graft with a new one made of different material has been reported to be effective [ 10 , 25 ]. Recent advancements in surgical intervention include fibrin glue applied to the graft [ 6 ], wrapping the graft using omentum [ 26 ] and endovascular relining of the prosthesis [ 27–29 ].…”
Section: Discussionmentioning
confidence: 99%